1989
DOI: 10.1161/01.res.64.5.977
|View full text |Cite
|
Sign up to set email alerts
|

Early afterdepolarizations: mechanism of induction and block. A role for L-type Ca2+ current.

Abstract: Early afterdepolarizations (EADs) are a type of triggered activity found in heart muscle. We used voltage-damped sheep cardiac Purkinje fibers to examine the mechanism underlying EADs induced near action potential plateau voltages with the Ca 2+ current agonist Bay K 8644 and the effect of several interventions known to suppress or enhance these EADs. Recently, we reported a model for inducing EADs in sheep and canine cardiac Purkinje fibers using the Ca 2+ current agonist Bay K 8644. 3 Bay K 8644 produced co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
387
2
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 631 publications
(413 citation statements)
references
References 48 publications
22
387
2
2
Order By: Relevance
“…It is well known that LCC window current is a key component for EADs (17)(18)(19)(20)(21), but all other currents during the plateau also contribute to the formation of the EADs (21,41). Using bifurcation analysis (21,44), we have previously identified the bifurcations that initiate and terminate the voltage oscillations, and characterized the contribution of each ionic current in generating these bifurcations.…”
Section: Modulations Of Eads By Ca Cycling Dynamicsmentioning
confidence: 99%
“…It is well known that LCC window current is a key component for EADs (17)(18)(19)(20)(21), but all other currents during the plateau also contribute to the formation of the EADs (21,41). Using bifurcation analysis (21,44), we have previously identified the bifurcations that initiate and terminate the voltage oscillations, and characterized the contribution of each ionic current in generating these bifurcations.…”
Section: Modulations Of Eads By Ca Cycling Dynamicsmentioning
confidence: 99%
“…Abnormal L-type Ca 2ϩ channel activity can cause EADs (24). Thus we examined the effects of NOS3 signaling on the I Ca in myocytes from WT and NOS3 Ϫ/Ϫ mice.…”
Section: Nos3 and Arrhythmogenesismentioning
confidence: 99%
“…1). Previous work has shown that EADs can result from abnormal I Ca activity (24). In addition to EADs, increased Ca 2ϩ influx via I Ca can also lead to aftercontractions.…”
Section: Nos3 and Arrhythmogenesismentioning
confidence: 99%
See 2 more Smart Citations